Sisyphus Cannot Rest. Ethical Challenges of Artificial Intelligence - Thiel, Volker (ETHICS IN PROGRESS, 2019)
The use of machines with artificial intelligence in different areas of life and the trend to develop a „homunculus“ makes ethical rating necessary. Starting with early rules of behavior and moral norms, traditions in the occidental ethic history will be presented and faced with the question, whether they can be of any help to understand artificial intelligence, and which conclusions should be considered while developing and using machines with (strong) artifical intelligence by individuals, states, and finally, the whole world.